2017
DOI: 10.1038/s41598-017-04489-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of Clistocoeloma sinensis (Brachyura: Grapsoidea): Gene rearrangements and higher-level phylogeny of the Brachyura

Abstract: Deciphering the animal mitochondrial genome (mitogenome) is very important to understand their molecular evolution and phylogenetic relationships. In this study, the complete mitogenome of Clistocoeloma sinensis was determined. The mitogenome of C. sinensis was 15,706 bp long, and its A+T content was 75.7%. The A+T skew of the mitogenome of C. sinensis was slightly negative (−0.020). All the transfer RNA genes had the typical cloverleaf structure, except for the trnS1 gene, which lacked a dihydroxyuridine arm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Sesarma and Clistocoeloma are part of Sesarmidae, Grapsoidea. These findings are in keeping with previous reports (Von Hagen, 1978;Tang et al, 2017;Xin et al, 2017a) We present evidence that both Helice species are significantly closer to most Varunidae genera than to the Sesarmidae based on the CO1 genes sequences, which is in accordance with the findings reported by Guinot (1978) and Schubart et al ( , 2000. Preliminary results show that the genus Varuna clusters with the other Varunidae species based on its 16S rRNA sequence (Schubart et al, , 2000.…”
supporting
confidence: 83%
“…Sesarma and Clistocoeloma are part of Sesarmidae, Grapsoidea. These findings are in keeping with previous reports (Von Hagen, 1978;Tang et al, 2017;Xin et al, 2017a) We present evidence that both Helice species are significantly closer to most Varunidae genera than to the Sesarmidae based on the CO1 genes sequences, which is in accordance with the findings reported by Guinot (1978) and Schubart et al ( , 2000. Preliminary results show that the genus Varuna clusters with the other Varunidae species based on its 16S rRNA sequence (Schubart et al, , 2000.…”
supporting
confidence: 83%
“…Comparative analysis of mitochondrial gene order has been proved to be a valuable phylogenetic tool in crustaceans (Shen, Tsang, Chu, Achituv, & Chan, ; Xin et al, ). Based on the comparative analysis of mitochondrial gene arrangement within Sessilia, Shen et al () found that Amphibalanus amphitrite (Balanidae) should cluster with Striatobalanus amaryllis (Archaeobalanidae) and Nobia grandis (Pyrgomatidae) instead of Megabalanus (Balanidae), resulting in nonmonophyly of the family Balanidae.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the comparative analysis of mitochondrial gene arrangement within Sessilia, Shen et al () found that Amphibalanus amphitrite (Balanidae) should cluster with Striatobalanus amaryllis (Archaeobalanidae) and Nobia grandis (Pyrgomatidae) instead of Megabalanus (Balanidae), resulting in nonmonophyly of the family Balanidae. Xin et al () examined the mitochondrial gene arrangements of infraorder Brachyura and suggested that Clistocoeloma sinensis may belong to the group Sesarmidae of the superfamily Grapsoidea and that C. sinensis and Sesarmops sinensis probably belong to sister groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of papers on the complete mitogenome of brachyuran species, the genomes of A. alayseae, A. rodriguezensis, Gandalfus yunohana and G. puia were downloaded from GenBank and included in reconstructed phylogenetic trees, all showing occurrence of T and A nucleotides that differed from that all of other studied Brachyura (Xin et al 2017a: 309;2017b;Tang et al 2017).…”
Section: Genetic Datamentioning
confidence: 99%